Synthesis and Preliminary Antimicrobial Study of 2-Amino-5-Mercapto-1,3,4-Thiadiazole Derivatives - Husam A. Ameen; Ahlam J. Qasir (College of Pharmacy University of Baghdad, 2017)
Nitrogen heterocycles are of a special interest because they constitute an important class of natural and non natural products, many of which exhibit useful biological activities.Among these nitrogen heterocycles are 1, 3, 4-thiadiazole containing compounds. The therapeutic effects of these derivatives have been well studied for a number of pathological conditions including inflammation, pain, or hypertension. Moreover, synthesis of thiadiazoles has attracted wide-spread attention due to their diverse applications as antibacterial, anticancer, antifungal anti-inflammatory and antidepressant agents.According to this informationâ€™s new derivatives of 1, 3, 4-thiadiazole were designed and synthesized and in the hope of having some activities as antibacterial and antifungal. These are: • 4-(((5-mercapto-1,3,4-thiadiazol-2-yl)imino)methyl)-2-methoxyphenol. • Tert-butyl (1- ((2- ((5- (methylsulfonyl) -1,3,4- thiadiazol-2-yl) amino) -2- oxoethyl)amino) -1-oxopropan - 2-yl) carbamate. Key words: 1, 3, 4-thiadiazole, biological activity, peptides, Schiff base.